Introduction to systems theory - Luhmann, Niklas, 1927-1998.; Baecker, Dirk.; Gilgen, Peter, 1963- (Cambridge, UK : Polity, 2013)
Niklas Luhmann ranks as one of the most important sociologists and social theorists of the twentieth century. Through his many books he developed a highly original form of systems theory that has been hugely influential in a wide variety of disciplines.In Introduction to Systems Theory, Luhmann explains the key ideas of general and sociological systems theory and supplies a wealth of examples to illustrate his approach. The book offers a wide range of concepts and theorems that can be applied to politics and the economy, religion and science, art and education, organization and the family. Moreover, Luhmann's ideas address important contemporary issues in such diverse fields as cognitive science, ecology, and the study of social movements.This book provides all the necessary resources for readers to work through the foundations of systems theory - no other work by Luhmann is as clear and accessible as this. There is also much here that will be of great interest to more advanced scholars and practitioners in sociology and the social sciences.
Includes bibliographical references (p. [255]-272) and index.
Keywords: Social systems; System theory